Quota Formula Review : Data Update and Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This appendix discusses the required data, the selection of the database, and the derivation of the data series used for the quota calculations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet